A Reflux Linked GATA Factor Fulcrum Dictates Lineage Commitment Through GPRC5B During the Esophageal Dysplastic TransitionSummary - Omar Abuhussein; Sara Hosseini-Farahabadi; Corina Stewart; Stephane Flibotte; Alireza Heravi-Moussavi; David Farnell; David Schaeffer; Fergal Donnellan; Frank McKeon; Wa Xian; Dermot Kelleher; Shane Patrick Duggan (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: GATA family transcription factors are somatically variable (SV) in esophageal adenocarcinomas (EAC) and inducible by simulated reflux. Our study examines the mechanisms whereby GATA family members (GATA4, GATA6, and the atypical TRPS-1) influence oncogenesis during the Barrett’s esophagus (BE) metaplasia-dysplasia transition preceding EAC. Methods: RNAseq analyses of esophageal cell lines and lesion-derived adult stem cells (ASCs) in conjunction shRNA- or CRISPR-facilitated gene silencing, together with reanalysis of The Cancer Genome Atlas data, spatial transcriptomics, and organ-on-a-chip studies were used. Results: Although a gastroesophageal reflux disease history positively correlated with GATA4/6 somatically variable and a columnar-associated gene signature (ANPEP/GATA4) in The Cancer Genome Atlas EAC cases, it negatively associated with a squamous lineage-linked signature (TP63/SOX15) containing TRPS1. In experimental data, opposing effects on regulators of squamous and columnar lineage identity were uncovered between TRPS1 and classical GATA factors (GATA4/6). Interrogation of this GATA “fulcrum” defined further genes (CGN, IL6R, and GPRC5B) targeted for TRPS1-mediated suppression or GATA4/6 activation. A novel spatial transcriptomic signature of BE-associated high-grade dysplasia (HGD) captured GATA fulcrum action, through GPRC5B expression. Functionally, GPRC5B was found to be low-pH-responsive, to increase proliferative and colony formation rates, and when overexpressed facilitate a hyperproliferative HGD-like transformation of BE-ASCs. Using an organ-on-a-chip platform, cellular overgrowth, reduced luminal villus structures, lower goblet cell numbers, and loss of intestine-associated marker gene expression (TFF3/MUC2) were observed following GPRC5B overexpression in BE-ASCs, mirroring HGD. Conclusions: This study identifies critical GATA factor-mediated processes underlying cellular phenotype in the BE-HGD-EAC transition and identifies GATA-inducible GPRC5B as a functional marker and possible driver of progression through HGD to EAC.